PENDAMPINGAN ALTERNATIF METODE PENJUALAN DAN REKOMENDASI PENGELOLAAN LIMBAH TEMBAKAU - Hadi Susilo, Joko; Handayani, Tri Astuti; Rahmawati, Laily Agustina; Astuti, Hartiningsih; Endang, Endang; Suprastiyo, Ahmad; Erwanto, Erwanto; Dawud, Moh. Yusuf; Abid, M. Alwi; Atmaja, Dimas Surya (Jurnal Abdi Masyarakat, 2024)
The aim of this assistance is to provide insight and knowledge about alternative ways of selling tobacco and recommend tobacco waste management to the younger generation in Banggle Village, Sukorame District, Lamongan Regency. The reason for determining the location and focus on mentoring the younger generation is to maintain the regeneration of tobacco farmers as a form of improving the quality of the agricultural sector in the future and at the same time the majority of farmers in Banggle Village are tobacco farmers. . Assistance is carried out in stages starting with basic observations in the field regarding the management and sales system of tobacco plants. The results of this assistance concluded that there were three sales methods, namely the direct sales system, the sales system through the enumeration stage using sugar additives and not using sugar additives. The most recommended sales method in this assistance is the sales system through the chopping stage using sugar additives, followed by the sales method through the chopping stage without using sugar additives and finally the alternative direct sales method. The results of the assistance recommended that the most appropriate management of tobacco waste is to use organic fertilizer. The evaluation results show a lack of resources that understand detailed calculations regarding tobacco sales methods.